Editorial Revista Colombiana de Entomología Vol. 44 No. 1, 2018. (2018)
In the search to offer a better service to our readers, we are announcing a strategic alliance with the editorial team of Universidad del Valle (Cali, Colombia). From this issue 44 (1), January-June 2018, the Revista Colombiana de Entomología (RCdE) begins a new era in which we aspire to continue spreading the entomological advances made in different latitudes, especially in Latin America and the Caribbean. From now and forward, we will stop publishing on paper, adjusting ourselves to the parameters of environmental and forest conservation, with new mechanisms in the editorial process, such as the submission platform online (on-line) and its respective publication, which will expedite the publication process. Of course, without detriment of our high peer review standards. As you can notice, the change to electronic publication implies a change in our ISSN, but the journal retains its name and continuity in volumes that represent 44 years of continuous publication. I express my gratitude to members of Socolen, the editors, professionals, designers, printers who made possible in a committed way the publication of RCdE to date in printed format. In the other hand, I would like to thank all the personnel linked to the editorial team of Universidad del Valle as well as to the editorial committee of RCdE and SOCOLEN executives for trusting in this initiative and supporting this transcendental step. I am quite sure, that this will represent a positive impact on the future of our journal. Finally, I would like to invite our readers and contributors to join this new stage so that together we can continue to make the RCdE one of the main and accredited organs of dissemination of entomological research.